Assessing variation in co-offending networks. Issue 1 (2nd January 2022) - Bright, David; Whelan, Chad; Ouellet, Marie
ABSTRACT: The current study aims to expand the geographic breadth of co-offending research by providing one of the first examinations of co-offending within Australia. We find co-offending was more common for some crimes than others. Individuals arrested for homicide had some of the highest co-offending rates and were more frequently observed in the core of the co-offending network. Females had higher rates of co-offending than males, and differences between sexes were most pronounced for sexual assault. However, females were underrepresented in the core of the network as compared to males. Lastly, co-offending declined with age, with the exception of drug offences for which co-offending was slightly more common among older age groups. Despite declines in co-offending overall, all age groups were equally represented in the network's core. Results emphasise the importance of disaggregating co-offending by crime type and examining co-offending across international contexts to better inform theory and policy.